PEMETAAN AKSES HALAMAN SITUS WEB BERBASIS LOG-ACCESS: STUDI KASUS WEB USAGE MINING DI SITUS perpus.akakom.ac.id - Librado, Dison; wagito, wagito (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2019)
Since the 2016, STMIK AKAKOM Library implements the information system thoroughly by using developed application that should connect to other library application. Various menu that provided is Home, Kontak, Tautan, Layanan, Profile, Katalog Online, and Digital Library. Research aims to determine the pattern of visits to the web and identify what pages are frequently visited by visitors Research begins with literature study of a relevant topic, configure the Nginx server, collecting log access data during a certain time, until prepared them so the result and conclusions can be achieve. In web usage mining implementation there are three stages that are carried out to get libraries and sources of information namely preprocessing, pattern discovery and pattern analysis. The research object is the STMIK AKAKOM library site. The results show which pages that most frequently visited is ‘Home’, ‘Berita’, ‘Digital Library’, ‘Koleksi’, Tautan’, ‘Layanan’, ‘Katalog Online’, dan ‘Kontak’. The operating system or browser that used much more is Windows, Android, Linux, and iphone. By Internet Protocol, the most visitors came in is from outside of Akakom